2018
DOI: 10.3390/vetsci5020049
|View full text |Cite
|
Sign up to set email alerts
|

Field Efficacy of an Attenuated Infectious Bronchitis Variant 2 Virus Vaccine in Commercial Broiler Chickens

Abstract: Egyptian poultry suffer from frequent respiratory disease outbreaks associated with Infectious Bronchitis Virus (IBV) variant 2 strains (Egy/VarII). Different vaccination programs using imported vaccines have failed to protect the flocks from field challenge. Recent studies confirmed a successful protection using homologous strains as live attenuated vaccines. In this study, a newly developed live attenuated IB-VAR2 vaccine representing the GI-23 Middle East IBV lineage was evaluated in day-old commercial broi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…Therefore, it seems to be very important to find sufficient alternatives for vaccination to improve the protection level. Recently, a new IB-VAR206 vaccine was proven infield to show a good efficacy to protect broilers from clinical illness after exposure to field virus (Elhady et al, 2018). Until now, this vaccine has not been approved in Europe and can thereby only be imported, having a special authorization from the responsible veterinary authorities.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it seems to be very important to find sufficient alternatives for vaccination to improve the protection level. Recently, a new IB-VAR206 vaccine was proven infield to show a good efficacy to protect broilers from clinical illness after exposure to field virus (Elhady et al, 2018). Until now, this vaccine has not been approved in Europe and can thereby only be imported, having a special authorization from the responsible veterinary authorities.…”
Section: Discussionmentioning
confidence: 99%
“…Especially in layer and breeder chickens, a decline in egg production alone can cause significant economic losses. However, IBV and NDV live vaccines probably mutually interfere with concurrent immunization [45][46][47]. Furthermore, a live-attenuated IBV vaccine is at risk of virulence recovery, contributing to emergence of new IBV variants.…”
Section: Discussionmentioning
confidence: 99%
“…However, protection studies indicated that homologous strain vaccines usually induce better protection against IBV challenge (2325). The field situation in Egypt indicates that the IBV variant 2 is the most predominant serotype in Egypt (2629), hence the newly developed vaccines using the variant 2 strain showed better protection againest homologous challenge under both expermintal and field situation (17, 30). The Egyptian variant-2 viruses shows high genetic difference to all IBV imported vaccines with multiple amino acid substitutions at virus neutralization (VN) epitopes (3133) that may explain the high frequency of IBV outbreaks in vaccinated flocks in Egypt.…”
Section: Introductionmentioning
confidence: 99%